Madrasah Sebagai Lembaga Pendidikan Islam (Sistem dan Perkembangannya Sebelum dan Sesudah Kemerdekaan) - Rahmat, Rahmat (Rihlah: Jurnal Sejarah dan Kebudayaan, 2014)
Madrasah is analternative educational institution for the parents to be the venue for the education of her son. The number of madrasah from one period to the next government has developed. Therefore, policy makers and others involved in the educational process at the school should pay attention to the learning systemas the early history of its formation. The Growth madrasah in Indonesia against the back drop of two factors; First, factors renewal of Islamic thought which responded by breathing santri who studied in the Middle East. The second is response to the Dutch government’s education policy. The development of madrasah before and after independence is determined policy authorities. Before independence policies adopted by the colonial government to wards education oriented to streng the rule of Islam in Indonesia. After independence, the Indonesian government to law the madrasah education with a number of regulations and legislation